A Qualitative Study of Camera Techniques and Visual Quality in Broadcasts of Pegadaian Liga 2 Football - Teguh Setiawan; Fayyadh Fauzan; Sheva Ronaldo; Restu Putria Nabila (Jurnal Ilmiah Multimedia dan Komunikasi, 2026)
Sports broadcasting production, particularly in Pegadaian Liga 2, still faces various challenges in maintaining visual quality. These challenges are caused by limitations in production equipment, changing field conditions, and less-than-optimal coordination among the production crew. This study aims to identify camera shooting techniques and the factors influencing visual quality in Pegadaian Liga 2 broadcast production. The research employed a descriptive qualitative approach using data collection techniques through in-depth interviews, observation, and documentation involving four broadcasting practitioners experienced in multi-camera sports broadcasting production. The data were analyzed using thematic analysis techniques through the processes of data reduction, categorization, interpretation, and conclusion drawing. The results show that visual quality is influenced by the cameraman’s ability to capture important moments, mastery of blocking camera techniques and shot composition, as well as teamwork and real-time communication among the crew. In addition, factors such as lighting, weather conditions, and equipment limitations also affect broadcast quality. The use of modern broadcasting technologies, such as super slow-motion and remote production, can help improve broadcast quality, although these technologies have not been implemented evenly. This study concludes that improving the broadcast quality of Pegadaian Liga 2 requires support through equipment upgrades, enhancement of crew competencies, and more optimal utilization of broadcasting technology.